The upper crustal thermal structure of the Cameli Basin and its surroundings (SW Anatolia, Türkiye) by using the fractal-based centroid method of aeromagnetic data and its relationship with earthquakes occurring in the region - Akar, Fahriye (Frontiers in Earth Science, 2024)
The Cameli Basin and its surroundings are located at the southwestern Anatolia of Turkey, and one of the tectonically active regions in western Turkey. The Curie point depth of continental crust can help us to determine the regional tectonic and geothermal structures. The aeromagnetic magnetic data of the study region were used to determine the Curie Point Depth estimates. The fractal based centroid method used for this purpose. The fractal approach removes the effect of fractal magnetization in the power spectrum. The depth to the bottom of the deepest magnetic sources in the study region range between 6.9 and 14.05. The estimated thermal gradient varies from 41.28°C/km to 89.23°C/km and average value is 58.59 °C/km (580°C for magnetite). The distributions of earthquakes are compatible with NW-SE trending estimated Curie depth anomalies. Interpretation indicates that the depth to the Curie isotherm is considerably shallower than the Moho depth.